MENINGKATKAN HASIL BELAJAR IPA SISWA PADA POKOK BAHASAN SISTEM PENCERNAAN DENGAN METODE DISKUSI DI KELAS V SDN 013 SIMANGAMBAT KECAMATAN SIABU - Miskah Miskah (Jurnal Guru Kita PGSD, 2017)
Abstract : Implementation of Jigsaw Learning Model as Teacher Effort Increase Participation Learning to Understand Poetry Reading for Elementary School Grade VI. This research was conducted at SDN 013 Simangambat, Siabu Sub-district, Mandailing Natal Regency. This type of research is Classroom Action Research by applying the method of discussion. This study aims to improve student learning outcomes in class V. This study was conducted in 2 cycles. The subject of this research is the students of grade V SDN 013 Simangambat with the number of 23 people. From the research, it is found that the improvement of the learning result after the action is done. The learning outcomes at prasiklus, the average class obtained by the students was 58.69 from 23 students 19 people got the score below the KKM (82.60%), 4 people completed (17.39%), the highest score 75 and the lowest score 37.5. In the first cycle, the average value of the class increased to 67.26 with 8 students scored below the KKM (34.78%) and 15 people scored above the KKM (62.21%), the lowest score of 53 with the highest score of 80. At cycle II the average grade value increased again to 70.17 with the highest score 93. From the improvement of the students obtained mastery can be concluded that the application of discussion methods can improve student learning outcomes.Keywords : Learning outcomes, Discussion Methods, ScienceAbstrak : Meningkatkan Hasil Belajar IPA Siswa Pada Poko Bahasan Sistem Pencernaan Dengan Metode Diskusi di Kelas V SDN 013 Simangambat Kecamatan Siabu. Penelitian ini dilaksanakan di SDN 013 Simangambat Kecamatan Siabu Kabupaten Mandailing Natal. Jenis penelitian ini adalah Penelitian Tindakan Kelas dengan menerapkan metode diskusi. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa di kelas V. Penelitian ini dilakukan dalam 2 siklus. Subjek penelitian ini adalah siswa kelas V SDN 013 Simangambat dengan jumlah 23 orang. Dari penelitian yang dilaksanakan diperoleh peningkatan hasil belajar setelah dilaksanakan tindakan. Hasil belajar pada saat prasiklus, rata-rata kelas yang diperoleh siswa adalah 58,69 dari 23 siswa 19 orang mendapat nilai di bawah KKM (82,60%), 4 orang tuntas (17,39%), nilai tertinggi 75 dan nilai terendah 37,5. Pada siklus I nilai rata-rata kelas meningkat menjadi 67,26 dengan 8 siswa memperoleh nilai di bawah KKM (34,78%) dan 15 orang memperoleh nilai di atas KKM (62,21%), nilai terendah 53 nilai tertinggi 80. Pada siklus II nilai rata-rata kelas meningkat lagi menjadi 70,17 dengan nilai tertinggi 93. Dari peningkatan ketuntasan yang diperoleh siswa dapat diambil kesimpulan bahwa penerapan metode diskusi dapat meningkatkan hasil belajar siswa.Kata Kunci : Hasil belajar, Metode Diskusi, IPA